Stressed and Unstressed Forms as Recognized by Iraqi EFL Arab and Kurdish University Students: A Sociolinguistic Study - Abood, Ajwad Thamir; Rizqallah, May S. (Al-Adab Journal, 2021)
This study aims to investigate the Iraqi EFL Arab and Kurdish University students’ ability to recognize the stressed (full or strong) forms and the unstressed (reduced or weak) forms within connected speech of English. The material chosen includes six auxiliary verbs. The sample of the study is twenty Iraqi EFL Arab and Kurdish fourth year university students of both genders (males and females). The participants are from the University of Baghdad and the University of Duhok.